URINARY INCONTINENCE IN ANTENATAL WOMEN AND ITS IMPACT ON QUALITY OF LIFE - Ismail, Ayesha; Parveen, Zahida; Sultana, Ruqqia; Iqbal, Hajira; Zeb, Sobia; Israr, Anaheeta (Journal of Ayub Medical College Abbottabad, 2026)
Background: The involuntary leakage of urine is key feature of urinary incontinence (UI), and is prevalent but underreported condition among pregnant women. Despite being benign, UI significantly affects physical, emotional, and social well-being, particularly in low-resource environments where continence care is often overlooked. Methods: A prospective cross-sectional study was done over six months in the Gynaecology C Unit at Ayub Teaching Hospital, Abbottabad. A total of 388 women with singleton pregnancies beyond 37 weeks were enrolled using a non-probability, sequential sampling technique. Data was collected using standardized tools, including International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF), Urogenital Distress Inventory (UDI-6), the Incontinence Impact Questionnaire (IIQ-7), and the SF-12v2 Health Survey. Variables assessed included symptom type, severity, impact on daily activities, and overall HRQoL. Results: UI symptoms were reported by majority of participants, with frequent urination (70.1%) and urinary incontinence (51.0%) being the most common. Stress incontinence was suggested by leakage triggered by coughing or sneezing (59%). Around 13.6% experienced severe to very severe symptoms. UI had a considerable impact on daily life, notably on household tasks (55.4%), emotional health (44.8%), and physical activities (48.5%). General health and quality of life were also negatively impacted, with 43% expressing continuous weariness and 32.5% ranking their health as fair or poor. Conclusion: UI is a common and disruptive condition during pregnancy, affecting many aspects of quality of life. Early identification, education, and incorporation of pelvic floor health into antenatal care are essential to improving maternal well-being and reducing postpartum complications.